Abortion And The Christian Tradition: A Pro-Choice Theological Ethic, by Margaret D. Kamitsuka - Chan, Michael J. (Word & world, 2021)
Word & World is a quarterly journal of theology whose readers are concerned with Christian ministry in and for the world.